Reliability of using stereo photogrammetry to estimate modal parameters - Sabino, Danilo Damasceno [UNESP]; Poozesh, Peyman; Pereira, Joao Antonio [UNESP]; Niezrecki, Christopher (Springer Nature, 2017)
Stereophotogrammetry is a three-dimensional full-field measurement technique that has gained more importance in the area of modal analysis in the past few years. In this technique, full-field data can be taken in a single snapshot, which can be considered a great advantage over conventional measurement techniques such as laser vibrometer and accelerometer. However, it is not clear whether the stereophotogrammetry data can provide accurate modal parameters for output-only systems identification applications. This work presents a study that integrates stereophotogrammetry with output-only systems identification aiming at evaluate the use of optical measurement data (stereophotogrammetry) to estimate the modal parameters. A comparative study of two output-only systems identification (Operational PolyMAX and Stochastic Subspace Identification) and ordinary input-output based method (PolyMAX) was carried out to verify the capability of output-only methods to work with stereophotogrammetry data. The Operational PolyMAX provided more clear stability diagram and accurate damping ratio when compared with the reference parameters, however, it missed some modes in the analysis, while SSI has been shown more robust to identify the whole modes in the analyzed frequency range.
Keywords: Digital image correlation; Operating deflection shapes; Operating modal analysis; Stereophotogrammetry